(untitled) (Architecture Image Studies, 2023)
Arif Paşa Mansion, whose restoration works have been completed recently, is located in Fatih District of Istanbul (in the old Eminönü).The building, which has been used with different functions since its construction, was first built as a mansion. This building, which was planned to be restored as the “Provincial Youth Assembly and Culture Mansion” by the Istanbul Metropolitan Municipality, was best known as the old Eminönü Municipality Building.It was built as a “mansion” in the late 19th century and became known as “Arif Pasha Mansion”. After a lavish life, it changed hands in 1911 and was used as the “Şehremanet” building ( Municipality Building). It became the command (headquarters) of the French occupation forces in 1918 and continued this function until 1923. It functioned as Turkey’s first “conservatory” in the 1930s. In the following years, it began to be used as an official institution. II. Mahmud Tomb, Cevri Kalfa Sibyan School, Firuz Ağa Mosque, Kaygusuz Lodge, Şehzade Mosque, Press Museum, Köprülü Library, Mosque, Madrasa and Tomb, Çemberlitaş Square, Atik Ali Paşa Mosque, Koca Sinanpaşa Complex, Çorlulu Ali Paşa Comp lex, Merzifonlu Kara This area, which is surrounded by historical buildings and squares such as the Pasha Complex, Gedik Ahmet Pasha Mosque, Bath, Million Stone, 1001 Mast Cistern and Çemberlitaş Bath, has been used as a settlement for ulema and rulers throughout history.This prepared text has been created in order to explain the method followed in the project studies carried out regarding the building, which also served as the ‘’Şehremaneti’’ for a period, and to summarize the process that occurred while presenting architectural solution proposals that would meet today’s needs by revealing its relationship with the historical environment.